The role of strategic leadership for learning on the relationship between training opportunities and salesperson job performance and commitment. Issue 9 (6th November 2018) - Lee, Jae Young; Welliver, Michele C.
Abstract : Purpose: The purpose of this study was to examine the indirect effects of strategic leadership for learning between sales employees' perceived learning opportunities and organizational commitment and job performance. Design/methodology/approach: A total of 204 responses from sales employees in a South Korean company were analyzed using path analysis to test the hypothesized model and hypotheses. Findings: Results of the analysis showed that strategic leadership has a significant indirect effect on the relationship between perceived learning opportunities and job performance and organizational commitment. Originality/value: The results of this study challenge the belief that providing learning opportunities improves salesperson performance and organizational commitment. The results indicate that the relationship between continuous learning opportunities and performance, as well as between opportunities and organizational commitment, is statistically nonsignificant. However, the authors did find that providing continuous learning opportunities via strategic leadership because learning increases performance and organizational commitment.